Sudan : Staff Report for the 2000 Article IV Consultation and Fourth Review of the First Annual Program Under the Medium-Term Staff-Monitored Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The macroeconomic objectives of the 1999 Staff-Monitored Program (SMP) have been broadly achieved in Sudan. The macroeconomic situation at the end of 1999 was modestly more expansionary than programmed. Budget expenditure was maintained below the program level throughout the year and a surge in oil prices in late 1999 has increased oil revenue above budgeted amounts. Broad money growth at end-December was roughly in line with the 1999 program. Both oil and non-oil revenue were strong in the first two months, and expenditure was below trend, allowing the government to build up deposits at the central bank.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet